Working longer the solution to the retirement income challenge - Munnell, Alicia Haydock (Brookings Institution Press, 2008)
"Investigates the prospects for moving the average retirement age to 66 from 63. Examines companies' incentives to employ older workers and what government can do to promote continued participation in the workforce. Considers the challenge of ensuring a secure retirement for low-wage workers and those unable to continue to work"--Provided by publisher.